Isolation and structure elucidation of potential cancer chemopreventive agents from Excoecaria Philippinensis merrill - Dator, Romel P.
The cancer chemopreventive potential of the crude extract, solvent fractions and isolates from Excoecaria philippinensis Merrill was evaluated using the DPPH free radical inhibition assay, JB 6 transformation, and HL 60 differentiation assays. Bioactivity-directed isolation and purification of the crude ethanol extract from the leaves of the plant, which revealed high bioactivities in the 3 assays, yielded two bioactive isolates namely, F2-4CB and F2-4DY. The isolate F2-4CB is an off-white amorphous solid and its structure was elucidated by NMR (1H NMR, 13C NMR, APT, HMQC, HMBC, H-H COSY), FT-IR, UV-VIS, elemental analysis, and HRMS. The isolate has a molecular weight of 184 amu and based on the elemental analysis it has a molecular formula of C8H8O5. Based on the spectral data, the isolate is methyl 3,4,5-trihydroxybenzoate or methyl gallate. A dimer peak was observed with a molecular weight of 368 amu. The isolate showed 99.07% DPPH inhibition at a concentration of 200 µg/mL and exhibited a dose dependent DPPH free radical inhibition with IC50 of 4.11 µg/mL comparable to the positive control gallic acid with IC50 of 3.03 µg/mL. The solvent control, DMSO showed 0.0% free radical inhibition at the same concentration. The isolate effectively blocked the transformation of the pre initiated murine epidermal JB 6 cells into a malignant phenotype at 4 µg/mL with 75.28% inhibition while the positive control retinoic acid exhibited 87.25% inhibition. The observed non cytotoxic activity of the isolate against the JB 6 cells evaluated using the MTT assay suggests that its anti transforming ability is due to its capacity to inhibit pre neoplastic transformation into a malignant phenotype rather than by directly killing the cells. The negative control DMSO inhibited JB 6 transformation at 4 µg/mL with only 0.89% inhibition. Furthermore, the isolate induced terminal differentiation of HL 60 leukemia cells determined by the NSE/SE assay with 57.18% differentiation at 4ug/mL and exhibited 43.43% NBT reduction at the same concentration. The positive control Vit. D3 exhibited 71.4% and 51.95% HL 60 differentiation determined by the NSE/SE and NBT assays, respectively. Differentiation of HL 60 cells observed was coupled with non proliferation of cells. The non cytotoxic activity evaluated using the trypan blue assay suggests that terminally differentiated cells stop dividing probably due to modulation of certain signal transduction pathways leading to cell cycle arrest during the induction of cell differentiation. The results of the bioassay suggest that the isolate F2-4CB being an antioxidant, could effectively inhibit JB 6 cell transformation by preventing and blocking harmful effects caused by reactive oxygen species during tumor initiation, promotion and progression. The differentiation of HL 60 leukemia cells induced by the isolate may be due to its possible involvement in certain biochemical pathways leading to cell differentiation and cell cycle arrest. This result confirms the correlation observed among antioxidants, the ability to inhibit pre neoplastic JB 6 cell transformation and induction of differentiation in leukemic cells. The isolate F2-4DY is a yellow amorphous solid and has a melting point of 191°C. The ESI mass spectrum of isolate revealed a base peak at m/z 282 corresponding to [M-H]¬and a dimer peak at m/z 565 corresponding to [2M-H]-. The FT-IR spectrum showed the presence of hydroxyl and carbonyl functionalities. The isolate exhibited 96.77% DPPH free radical inhibition at 200 µg/mL. It was not subjected to the JB 6 and HL 60 assays due to its very low yield. The 1H NMR, 13C NMR, FT-IR, ESI-MS and UV-VIS data are not sufficient to propose the structure of the isolate. Further NMR analyses are needed to elucidate its structure. The isolates F2-4CB and F2-4DY from Excoecaria philippinensis Merrill could be potential candidates as cancer chemopreventive